Bladder leiomyoma: diagnostics, laparoscopy, and treatment - Godlewski, Dominik; Pszczółkowski, Patryk; Fedus, Tadeusz; Aebisher, David (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Leiomyosarcoma is the most common benign tumor of the bladder. However, it is only a small percentage of all proliferative changes of this organ. Aim. Presentation based on two clinical cases of diagnostics and surgical treatment from laparoscopic access of bladder leiomyoma. Description of the cases. Case 1. The work contains a diagnosis based on transvaginal ultrasound (TVUS), cystoscopy and computed tomography (CT), as well as partial laparoscopic bladder re section of leiomyoma in young women. Case 2. The case of young women with the histopathological result confirmed bladder leiomyoma. Conclusions. Leiomyoma is a rare bladder cancer. Laparoscopic bladder resection is a safe method that leads to healing.
Keywords: bladder leiomyoma; endometriosis; laparoscopic surgery